Szervezeti relációk a japán ipari vállalkozási kultúrában: A szégyen és bűntudat kultúrája: szervezeti normák és funkcióik - Balogh, Mónika (Távol-keleti Tanulmányok, 2020)
The present article develops a practical operational view of Ruth Benedict’s shame and guilt culture concept as one of the attributes which might characterize the structure and operation of Japanese social groups. After giving a short overview of critical approaches to this concept, several norm-forming, normoperating and sanctioning practices are examined in relation to the aspect of shame and guilt reactions from the everyday lives of intercultural industrial organizations (companies) located in Hungary, featuring Japanese company cultural elements in their operation. The evaluation and analysis of several related phenomena are conducted on the basis of fieldwork, involving further sociological concepts such as relational subjectivism, kanjin 閑人, shikaku 資格 and ba 場, chū 忠 and kō 孝, giri 義理 and ninjō 人情, wa 和, amae 甘えand others.